2021
DOI: 10.1245/s10434-021-10800-w
|View full text |Cite
|
Sign up to set email alerts
|

Oncoplastic Breast-Conserving Surgery for Synchronous Multicentric and Multifocal Tumors: Is It Oncologically Safe? A Retrospective Matched-Cohort Analysis

Abstract: Background Oncoplastic surgery is a well-established approach that combines breast-conserving treatment for breast cancer and plastic surgery techniques. Although this approach already has been described for multicentric and multifocal tumors, no long-term oncologic follow-up evaluation and no comparison with patients undergoing mastectomy have been published. This study aimed to evaluate whether oncoplastic surgery is a safe and reliable treatment for managing invasive primary multicentric and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…The implications of this study 4 are quite significant. As with past studies noting the success of oncoplastic surgery in pushing the boundaries of breast conservation in larger cancers, 5,6 the paper by De Lorenzi et al 4 suggests that, even in situations with multiple cancers, oncoplastic surgery may provide a breast conservation option for the patient. The results of this study supporting the safety of oncoplastic surgery add additional complexity to the treatment options in multifocal or multicentric breast surgery.…”
Section: Tufts Medical Center Bostonmentioning
confidence: 93%
See 3 more Smart Citations
“…The implications of this study 4 are quite significant. As with past studies noting the success of oncoplastic surgery in pushing the boundaries of breast conservation in larger cancers, 5,6 the paper by De Lorenzi et al 4 suggests that, even in situations with multiple cancers, oncoplastic surgery may provide a breast conservation option for the patient. The results of this study supporting the safety of oncoplastic surgery add additional complexity to the treatment options in multifocal or multicentric breast surgery.…”
Section: Tufts Medical Center Bostonmentioning
confidence: 93%
“…Furthermore, the relative fiscal impact of each choice with specific regards to financial toxicity to the patient has yet to be studied in detail, but is definitely a significant real-world issue that impacts decision-making. 9 In sum, De Lorenzi et al 4 provide an excellent study noting the comparable oncologic safety of oncoplastic surgery to mastectomy in multifocal and multicentric breast cancer.…”
Section: Tufts Medical Center Bostonmentioning
confidence: 99%
See 2 more Smart Citations
“…The study results showed that the disease-free and the overall survival rates were similar in the two groups suggesting that the oncoplastic approach is safe and effective for multifocal and multicentric breast cancer. 4…”
Section: Presentmentioning
confidence: 99%